2004
DOI: 10.1079/par2004358
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitin–proteasome-dependent proteolysis in the remodelling of skeletal muscle

Abstract: In skeletal muscle, as in any mammalian tissue, protein levels are dictated by relative rates of protein synthesis and breakdown. Recent studies have shown that the ubiquitin-proteasome-dependent proteolytic pathway is mainly responsible for the breakdown of myofibrillar proteins. In this pathway proteins that are to be degraded are first tagged with a polyubiquitin degradation signal. Ubiquitination is performed by the ubiquitin-activating enzyme, ubiquitin-conjugating enzymes and ubiquitin-protein ligases, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 25 publications
3
54
0
1
Order By: Relevance
“…Proteolysis by the proteasome is an ubiquitin-dependent process; poly-ubiquitinated proteins are subsequently recognised by the proteasome, which then degrades them (Taillandier et al, 2004). This process is ATP-dependent requiring a number of enzymes to ubiquitinate target proteins.…”
Section: Proteolytic Systems and Meat Qualitymentioning
confidence: 99%
“…Proteolysis by the proteasome is an ubiquitin-dependent process; poly-ubiquitinated proteins are subsequently recognised by the proteasome, which then degrades them (Taillandier et al, 2004). This process is ATP-dependent requiring a number of enzymes to ubiquitinate target proteins.…”
Section: Proteolytic Systems and Meat Qualitymentioning
confidence: 99%
“…This topic was covered by Dr Attaix (Taillandier et al 2004). The ubiquitin-proteasome-dependent proteolytic machinery is one of the major proteolytic systems in the skeletal muscle.…”
Section: Kip1mentioning
confidence: 99%
“…Since concentrations of LA and residual carbohydrate at 48 h postmortem varied among the sample groups, we calculated the corresponding glycolytic potential (GP) of each group based on LA and residual glucose concentrations to P.NYam-oSoret al In rat muscle, ubiquitin conjugates were reportedly increased 50-250% after food deprivation (Wing et al, 1995), but the precise substrates were poorly characterized (Taillandier et al, 2004). Immonen et al (2000c) found that beef bulls lost 11-33 mmol/kg glycogen during processing from the farm to slaughter depending on the diet and season.…”
Section: Methodsmentioning
confidence: 99%